THE EFFECT OF AI ON ENGLISH LANGUAGE RESEARCH QUALITY OF PALESTINIAN GRADUATE STUDENTS - Amani Abed (An-Najah National University, 2025)
‏This study aimed to investigate the effect of artificial intelligence (AI) tools on the quality of English-language academic research as perceived by Palestinian graduate students. Due to the lack of local research on the impact of AI on academic work, this study revealed students’ perspectives on using AI tools in research writing, focusing on their strengths, weaknesses, and strategies for maximize use. ‏A descriptive quantitative approach was selected, and data were collected through a questionnaire distributed electronically. The study sample included 171 valid responses from Palestinian graduate students .The instrument assessed high reliability, with a Cronbach’s Alpha coefficient of 0.907. Data analysis indicated that students generally had positive perceptions regarding the effect of AI tools in academic contexts. The overall mean score across the three domains reached 3.58 (71.6%), indicating a high level of perceived effectiveness. Participants particularly appreciated AI tools for saving time, enhancing language accuracy, and organizing information, while issues were raised regarding credibility, limited access, and AI’s difficulty in understanding context. ‏The study recommended adapting a balanced approach that combines AI support with students’ own efforts. It also referred the significant of providing training sessions on ethical and effective AI use and increasing institutional reach to AI tools within higher education.
أثر الذكاء الاصطناعي على جودة البحث العلمي في اللغة الإنجليزية لطلبة الدراسات العليا